Mini‐ and macro‐scale direct perfusion bioreactors with optimized flow for engineering 3D tissues. Issue 2 (5th December 2022) - Born, Gordian; Plantier, Evelia; Nannini, Guido; Caimi, Alessandro; Mazzoleni, Andrea; Asnaghi, M. Adelaide; Muraro, Manuele G.; Scherberich, Arnaud; Martin, Ivan; García‐García, Andrés
Abstract: Bioreactors enabling direct perfusion of cell suspensions or culture media through the pores of 3D scaffolds have long been used in tissue engineering to improve cell seeding efficiency as well as uniformity of cell distribution and tissue development. A macro‐scale U‐shaped bioreactor for cell culture under perfusion (U‐CUP) has been previously developed. In that system, the geometry of the perfusion chamber results in rather uniform flow through most of the scaffold volume, but not in the peripheral regions. Here, the design of the perfusion chamber has been optimized to provide a more homogenous perfusion flow through the scaffold. Then, the design of this macro‐scale flow‐optimized perfusion bioreactor (macro‐Flopper) has been miniaturized to create a mini‐scale device (mini‐Flopper) compatible with medium‐throughput assays. Computational fluid dynamic (CFD) modeling of the new chamber design, including a porous scaffold structure, revealed that Flopper bioreactors provide highly homogenous flow speed, pressure, and shear stress. Finally, a proof‐of‐principle of the functionality of the Flopper systems by engineering endothelialized stromal tissues using human adipose tissue‐derived stromal vascular fraction (SVF) cells has been offered. Preliminary evidence showing that flow optimization improves cell maintenance in the engineered tissues will have to be confirmed in future studies. In summary, two bioreactor models with optimized perfusion flow and complementary sizes have been proposed that might be exploited to engineer homogenous tissues and, in the case of the mini‐Flopper, for drug testing assays with a limited amount of biological material. Graphical Abstract and Lay Summary: Bioreactors enabling direct perfusion of cell suspensions or culture media through the pores of 3D scaffolds have long been used in tissue engineering to improve cell seeding efficiency as well as uniformity of cell distribution and tissue development. Here, two bioreactor models with optimized perfusion flow (Flopper) and complementary sizes that might be exploited to engineer homogenous tissues and, in the case of the mini‐Flopper (graphical abstract), for drug testing assays with a limited amount of biological material have been proposed.